The Association Between Irregular Sleep Patterns and Learning Outcomes: Implications for Students’ Health in Iraq - Ali, Hazhmat; Musa, Dildar Haji; Mohammed, Ary Habeeb; Abdulraheem, Hiwa; Salahadeen, Sherzad; Mustafa, Alind (Makara Journal of Health Research, 2025)
Background: Students often exhibit irregular sleep patterns due to rigorous academic workloads, which exert a considerable negative impact on their mental health. The present study aims to investigate the influence of irregular sleep on academic performance. Methods: This study recruited a cohort of 409 medical students of both genders. Upon their consent, participants filled out a closed-ended questionnaire on various sleep parameters, including sleep habits, duration, and environment. Results: Students with irregular sleep patterns reported higher rates of sleep deprivation, late sleep onset, and troubled sleep. Moreover, they spent a longer duration using smart devices before bedtime and experienced higher levels of stress. Irregular sleep demonstrated a positive correlation with sleep deprivation, sleep duration, troubled sleep, and the duration of smart device use (p = 0.000), energy drink consumption (p = 0.040), and junk-food intake (p = 0.000). Students exhibited poor academic performance, frequently experienced fatigue, and were unfocused. Irregular sleep was positively correlated with overall academic performance (p = 0.002), fatigue, and focus in class (p = 0.000). Conclusion: The findings indicate a significant impact of irregular sleep on learning outcomes and mental health among medical students. Thus, effective strategies are critically required to enhance sleep within this population.